Teachers’ Self-Perception and Practice of Social-Emotional - Mohamed, Suziyani; Abu Bakar, Kamariah; Yunus, Faridah; Nadirah Ibrahim, Siti Nur (International Journal of Psychosocial Rehabilitation, 2020)
Daily experiences play a significant role in the social-emotional development of young children. Social-emotional development did not grow naturally, but it needs to be nurtured and strengthened by individuals around the children. Preschool teachers as first children’s educators must be knowledgeable and practising a good social-emotional skill to stimulate social-emotional development. Therefore, this study aims to determine the level of teachers’ self-perception and practice regarding social-emotional development. This study also investigates the relationship between teachers’ self-perception and practice regarding social-emotional development. Survey research design with a quantitative approach was conducted. A self-developed questionnaire was used for data collection and 313 preschool teachers participated in the study. A descriptive and inferential statistics using Statistical Package for Social Science were performed to analyze the data. Result show preschool teachers demonstrate moderate self-perception and practice of social-emotional development. Pearson correlation analysis shows there is a strong, significant and positive relationship between teachers’ self-perception and practice. This finding shows teachers’ self-perception of social-emotional development will positively influence teachers’ practice in the classroom. Therefore, more in-service courses on social-emotional development should be held to empower and enhance teachers’ competency. Keywords— Preschool teacher, Social-emotional, Self-perception, Practices.